Teachers’ perceptions of the role of group cohesion for pupils’ well-being and learning environment in Finland - Lauri, Emma (My University, 2025)
This study investigated Finnish teachers’ perception of group cohesion, pupils’ well-being and learning environment in their classrooms and the relationship between these perceptions. The study aimed to show how these perceptions take place and how they are related in order to draw implications for pupils and classrooms. The study was conducted as a survey (N = 69) that included 24 items about teachers’ perceptions of group cohesion, well-being and learning environment and three open-ended questions about these. The survey was constructed by taking into consideration the literature and the national health survey by THL. The data was analysed using both quantitative and qualitative methods. The results suggest that teachers perceive group cohesion as important, their pupils’ well-being in their classrooms as positive, and learning environment in their classrooms as slightly positive. In addition, teachers’ perceptions of group cohesion correlated positively with their perceptions of their pupils’ well-being and the perceptions of learning environment in their classrooms. Based on this study, more research is needed to investigate the connection of group cohesion and pupils’ well-being and learning in Finland.
Keywords: group cohesion, well-being, learning environment, Finland, teachers, perceptions